Pension Funds and National Saving - Lopez Murphy, Pablo; Musalem, Alberto R. (World Bank, Washington, D.C., 2013)
The authors conduct an empirical study on the effect of the accumulation of pension fund financial assets, on national saving, using a panel of 43 industrial, and developing countries. The authors find evidence suggesting that the accumulation of pension fund financial assets might increase national saving, when these funds are the result of a mandatory pension program. By contrast, national saving might be unaffected, when pension funds are the result of a public program, implemented to foster voluntary pension saving.